Transcriptomic response of Mytilus coruscus mantle to acute sea water acidification and shell damage - Liao, Zhi; Liu, Fei; Wang, Ying; Fan, Xiaojun; Li, Yingao; He, Jianyu; Buttino, Isabella; Yan, Xiaojun; Zhang, Xiaolin; Shi, Ge (Frontiers in Physiology, 2023)
Mytilus coruscus is an economically important marine calcifier living in the Yangtze River estuary sea area, where seasonal fluctuations in natural pH occur owing to freshwater input, resulting in a rapid reduction in seawater pH. In addition, Mytilus constantly suffers from shell fracture or injury in the natural environment, and the shell repair mechanisms in mussels have evolved to counteract shell injury. Therefore, we utilized shell-complete and shell-damaged M. coruscus in this study and performed transcriptomic analysis of the mantle to investigate whether the expression of mantle-specific genes can be induced by acute seawater acidification and how the mantle responds to acute acidification during the shell repair process. We found that acute acidification induced more differentially expressed genes (DEGs) than shell damage in the mantle, and the biomineralization-related GO terms and KEGG pathways were significantly enriched by these DEGs. Most DEGs were upregulated in enriched pathways, indicating the activation of biomineralization-related processes in the mussel mantle under acute acidification. The expression levels of some shell matrix proteins and antimicrobial peptides increased under acute acidification and/or shell damage, suggesting the molecular modulation of the mantle for the preparation and activation of the shell repairing and anti-infection under adverse environmental conditions. In addition, morphological and microstructural analyses were performed for the mantle edge and shell cross-section, and changes in the mantle secretory capacity and shell inner film system induced by the two stressors were observed. Our findings highlight the adaptation of M. coruscus in estuarine areas with dramatic fluctuations in pH and may prove instrumental in its ability to survive ocean acidification (OA).